FRAIL Scale: an independent predictor of in-hospital mortality among older adults - TUFAN ÇİNÇİN, ASLI (My University, 2023)
OBJECTIVE: To screen for geriatric syndromes in older in-hospital patients and investigate their relationship with mortality. PATIENTS AND METHODS: Demographic data, comorbidities, and medical history of the patients were recorded. Anthropometric measurements were obtained at 72 hours after hospital admission. The Mini Nutritional Assessment-Short Form, strength, assistance with walking, rising from a chair, climbing stairs, and falls (SARC-F) sarcopenia screening questionnaire, Katz Activities of Daily Living scale, Lawton-Brody instrumental activities of daily living scale, the fatigue, resistance, ambulation, illness, and loss of weight (FRAIL) scale and the Eating Assessment Test-10 (EAT-10) screening test were used to assess geriatric syndromes. All patients were evaluated for delirium, pain, falls, polypharmacy, sleep disorders, incontinence, and pressure injury by the same researcher. RESULTS: A total of 85 patients were included in the study. The mean age was 75±7 years (range: 66-97). During hospital follow-up, 15.3% (n=13) of the patients died and 84.7% (n=72) were discharged. The median length of stay was 19 days (range: 3-126 days). In the multivariate analysis, frailty (hazard ratio: 2.67, 95% CI: 1.41-5.06, p=0.003) was found to be associated with in-hospital mortality. CONCLUSIONS: Frailty is an independent risk factor for in-hospital mortality in older adults.
Keywords: Temel Eczacılık Bilimleri; Eczacılık; Yaşam Bilimleri; Sağlık Bilimleri; Temel Bilimler; Basic Pharmaceutics Sciences; Pharmacology and Therapeutics; Life Sciences; Health Sciences; Natural Sciences; Yaşam Bilimleri (LIFE); Farmakoloji ve Toksikoloji; FARMAKOLOJİ VE ECZACILIK; Life Sciences (LIFE); PHARMACOLOGY & TOXICOLOGY; PHARMACOLOGY & PHARMACY; Farmakoloji (tıbbi); Pharmacology (medical)